2018
DOI: 10.1007/s00217-018-3033-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of black tea fractions addition on dough characteristics, textural properties and shelf life of wheat bread

Abstract: Theanine (T) and polyphenols (P) enriched fractions obtained from decaffeinated black tea dust by fractionation on a XAD resin, were incorporated into wheat bread formulation. The effect on dough properties and quality characteristics of supplemented breads was investigated. The development time and mixing resistance of dough was significantly increased by P fraction addition, indicating a stronger dough structure. P inhibited the Gram-positive bacteria, while E. coli was only inhibited by T fraction. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Studies by Schmitz, Weidenboerner, and Kunz () have shown that 2% of ground oregano inhibits the growth of Alternaria , Fusarium , Penicillium, and Aspergillu s. By the end of the storage, all samples revealed pronounced ( p < .05) Y & M growth, however, comparatively slower growth rate were observed in treatments than control pertaining to higher phenolic content of herbs. Culetu, Duta, and Andlauer () also reported proliferation of Y & M in stored breads; however, the count of yeast and mold in treatment remained significantly lower than control. In a study, on wheat breads a log 4 cfu/g yeast and molds count was attained in 8 days of storage (Latou, Mexis, Badeka, & Kontominas, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Schmitz, Weidenboerner, and Kunz () have shown that 2% of ground oregano inhibits the growth of Alternaria , Fusarium , Penicillium, and Aspergillu s. By the end of the storage, all samples revealed pronounced ( p < .05) Y & M growth, however, comparatively slower growth rate were observed in treatments than control pertaining to higher phenolic content of herbs. Culetu, Duta, and Andlauer () also reported proliferation of Y & M in stored breads; however, the count of yeast and mold in treatment remained significantly lower than control. In a study, on wheat breads a log 4 cfu/g yeast and molds count was attained in 8 days of storage (Latou, Mexis, Badeka, & Kontominas, ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al (2016) reported that the addition of black tea increased antioxidant capacity and reduced the formation of mould during storage, but altered the colour and increased surface roughness of Chinese steamed bread. Culetu et al (2018) observed that polyphenols enriched fraction from decaffeinated black tea dust contributed to darker, coarser and harder bread crumb structure and lower loaf volume in wheat bread. Ning et al (2017) showed that crumb hardness, cell diameter and chewiness of whole-wheat flour pan bread increased at higher green tea powder levels, while specific volume and brightness decreased.…”
Section: Introductionmentioning
confidence: 93%
“…The polyphenol fraction was found to inhibit the growth of Staphylococcus aureus , Bacillus cereus and Bacillus spizizenii while the theanine fraction inhibited the growth of Escherichia coli . The “control” sample deteriorated by the fourth day, yet the polyphenol and theanine‐enriched breads were preserved until the 8th and 5th day of storage respectively (Culetu et al ., ).…”
Section: Effects Of Refinement Of Flour Thermal Processing (Baking) mentioning
confidence: 97%
“…Cereal/grain sprouting/germination enhances bioactivity and thus increases the health‐promoting benefits of whole grains (Nelson et al ., ; Ding et al ., ). Despite the beneficial health‐promoting effects derived from the consumption of bread formulated with functional ingredients, baking (Bajerska et al ., ; Sun‐Waterhouse et al ., ) and storage (Yoon et al ., ; Culetu et al ., ) also impact on the bioactive properties of functional bread. This emphasizes the need to explore appropriate technologies that could enhance the bioactive content of functional bread.…”
Section: Introductionmentioning
confidence: 99%